Prospek Penjatuhan Putusan Provisi dalam Perkara Pengujian Undang-Undang - Iskandar Muda (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Provisional petition is not common in judicial review cases. This paper seeks to find the basis for submitting a provisional petition and the pattern of ruling on the provisional petition. The results showed that there were three things that became the basis for the petition for provisions, namely: (i) there were allegations of criminal acts in the formation of the law that was petitioned for review; (ii) protecting the constitutional rights which are seriously threatened and cannot be restored in the final judgment; and (iii) the urgent need for time to obtain a judge’s decision before the election, especially with regard to the right to vote and be elected. There were three pattern of rendering decisions on provisional petition, namely (i) dropped when the case examination process is ongoing and stated in writing before making the final decision; (ii) pronounced orally in court when the case examination process is ongoing and then reaffirmed in writing in the final decision; and (iii) decided simultaneously with the subject matter of the petition in the final judgment.